Trask's historical linguistics - Millar, Robert McColl, 1966-; Trask, R. L. (Robert Lawrence), 1944-2004. (London : Routledge, 2015)
'Trask's Historical Linguistics is an approachable and engaging introduction to historical linguistics - the study of language change over time. This third edition discusses language change, linguistic reconstruction, the birth and death of languages using language examples from around the world. Updated chapters on morphological change and the latest developments in sociolinguistic explanations of variation and change, as well as a brand new companion website with materials for both professors and students, make this third edition of Trask's Historical Linguistics indispensable for all students of language, linguistics and related disciplines'--
Includes bibliographical references and index.
Keywords: Historical linguistics; Comparative linguistics